How much load flexibility can a euro buy? Findings from a choice experiment with companies in the German commerce and services sector - Mark Olsthoorn; Joachim Schleich; Katharina Wohlfarth; Marian Klobasa (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2018)
Demand-side load management is considered a cost-efficient solution for ac-commodating growing shares of intermittent renewable electricity production. Here, we use double-bounded dichotomous choice (DBDC) contingent valua-tion (CV) to estimate the effectiveness of a subsidy for companies to make available their HVAC and cooling systems for automated load management. Our sample includes 1131 companies in the German commerce and services sector with Ï10 employees of which we elicit the willingness to accept (WTA) automated load management in exchange for an annual subsidy payment. To our knowledge, our study is the first CV study on load management among companies.
urn:nbn:de:0011-n-5183710
Keywords: 330; load management; demand response; subsidies; contingent valuation